KEPUASAN PELANGGAN MEMEDIASI SERVICESCAPE DAN PERSEPSI HARGA TERHADAP MINAT BELI ULANG - Fanya Adela; Titiek Tjahja Andari; Tini Kartini (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
In the service industry, company developments force professionals to stay abreast of the latest developments to compete. Customer happiness is a method that can be applied to maintain company survival by encouraging repurchase intentions. This research uses customer satisfaction at The Bucketlist Indonesia to test how price perceptions and servicescape influence repurchase intentions. Using a purposive sampling approach combined with a non-probability sampling strategy, the research sample consisted of 100 respondents. In this research, the analysis techniques used are quantitative, descriptive, and verification. Data analysis with the IBM SPPS Version 25.00 application utilizes path analysis and Sobel Test analysis. In conclusion, customer satisfaction can mediate servicescape and price perceptions on repurchase intention.